N-Cadherin Upregulation Promotes the Neurogenic Differentiation of Menstrual Blood-Derived Endometrial Stem Cells. (5th March 2018) - Liu, Yanli; Yang, Fen; Liang, Shengying; Liu, Qing; Fu, Sulei; Wang, Zhenyu; Yang, Ciqing; Lin, Juntang
Abstract : Peripheral nerve injuries are typically caused by either trauma or medical disorders, and recently, stem cell-based therapies have provided a promising treatment approach. Menstrual blood-derived endometrial stem cells (MenSCs) are considered an ideal therapeutic option for peripheral nerve repair due to a noninvasive collection procedure and their high proliferation rate and immunological tolerance. Here, we successfully isolated MenSCs and examined their biological characteristics including their morphology, multipotency, and immunophenotype. Subsequent in vitro studies demonstrated that MenSCs express high levels of neurotrophic factors, such as NT3, NT4, BDNF, and NGF, and are capable of transdifferentiating into glial-like cells under conventional induction conditions. Moreover, upregulation of N-cadherin (N-cad) mRNA and protein expression was observed after neurogenic differentiation. In vivo studies clearly showed that N-cad knockdown via in utero electroporation perturbed the migration and maturation of mouse neural precursor cells (NPCs). Finally, a further transfection assay also confirmed that N-cad upregulation in MenSCs results in the expression of S100. Collectively, our results confirmed the paracrine effect of MenSCs on neuroprotection as well as their potential for transdifferentiation into glial-like cells and demonstrated that N-cad upregulation promotes the neurogenic differentiation of MenSCs, thereby providing support for transgenic MenSC-based therapy for peripheral nerve injury.